(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
descriptive qualitative research aims to analyze the patterns of speaking errors exhibited by ten sixth-semester students in the English Education Study Program at Universitas Negeri Manado. Data were collected during business plan presentations in the English for Business and Public Presentation course. Data collection involved audio-visual recordings and participant observation, which were then transcribed verbatim. The subjects of this study were ten sixth-semester students enrolled in the English for Business and Public Presentation course. Data analysis was conducted inductively by identifying, categorizing, and deeply analyzing each speaking error identified in the transcripts. Based on the findings, the students made some dominant grammatical errors, significant fluency disturbances (including frequent pauses and false starts), and lexical and syntactic challenges, such as incomplete sentences and inappropriate verb forms. This study highlights the diagnostic potential of speaking error analysis in identifying challenges in foreign language processing. Pedagogically, these findings recommend focused teaching interventions to develop automatic oral fluency and practical strategic competence, better preparing students for English for Specific Purposes (ESP) communication.